Stem cells propagate their DNA by random segregation in the flatworm Macrostomum lignano. - Freija Verdoodt; Maxime Willems; Stijn Mouton; Katrien De Mulder; Wim Bert; Wouter Houthoofd; Julian Smith; Peter Ladurner (PLoS ONE)
Adult stem cells are proposed to have acquired special features to prevent an accumulation of DNA-replication errors. Two such mechanisms, frequently suggested to serve this goal are cellular quiescence, and non-random segregation of DNA strands during stem cell division, a theory designated as the immortal strand hypothesis. To date, it has been difficult to test the in vivo relevance of both mechanisms in stem cell systems. It has been shown that in the flatworm Macrostomum lignano pluripotent stem cells (neoblasts) are present in adult animals. We sought to address by which means M. lignano neoblasts protect themselves against the accumulation of genomic errors, by studying the exact mode of DNA-segregation during their division. In this study, we demonstrated four lines of in vivo evidence in favor of cellular quiescence. Firstly, performing BrdU pulse-chase experiments, we localized 'Label-Retaining Cells' (LRCs). Secondly, EDU pulse-chase combined with Vasa labeling demonstrated the presence of neoblasts among the LRCs, while the majority of LRCs were differentiated cells. We showed that stem cells lose their label at a slow rate, indicating cellular quiescence. Thirdly, CldU/IdU- double labeling studies confirmed that label-retaining stem cells showed low proliferative activity. Finally, the use of the actin inhibitor, cytochalasin D, unequivocally demonstrated random segregation of DNA-strands in LRCs. Altogether, our data unambiguously demonstrated that the majority of neoblasts in M. lignano distribute their DNA randomly during cell division, and that label-retention is a direct result of cellular quiescence, rather than a sign of co-segregation of labeled strands.